Regional devolopment and solidarity in Spain: the relationship between the E.C. and the internal solidarity funds. - Santiago Alvarez-García; Antonio Aparicio-Perez; Ana Isabel González (European Regional Science Association (ERSA), 2004)
This paper will analyse the importance that the Regional Solidarity Funds have acquired in the financial systems of those Autonomous Communities able to benefit from them, and the influence that these Funds have had in their development. In addition, the special role that Structural Funds have had in order to bring the Autonomous Communities' development in line with the average level of the European Member States will be referred to. Then, the different EC tools that are connected with regional development will be described and analysed; next, the Spanish regions that have benefited from these tools since Spain joined the European Union in 1986 will be studied. The Internal Solidarity Funds and their relationship with the EC Structural Funds will also be analysed. The effects of these mechanisms will be examined from three different points of view. First of all, the impact of these resources on the regional financial system will be considered; secondly, the coordination between the EC Structural Funds and the Internal Solidarity Funds, and the impact of this relationship will be analysed; and finally, whether or not these mechanisms are efficient enough to achieve the aim of regional unity will be determined, and their influence in different areas of production will also be observed. Key words: Fiscal Federalism, Spanish Autonomous Communities, Structural Funds, Inter-regional Solidarity. JEL Codes: H7, H77.
Keywords: H7; H77; 330; Fiscal Federalism; Spanish Autonomous Communities; Structural Funds; Inter-regional Solidarity